Defibrillator with Monophasic and Biphasic Fibrillation Signal - Wijaya, I Gusti Bagus Aditya; Wijaya, Aditya; Yulianto, Endro; Kholiq, Abd (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2019)
Lack of knowledge about functions, working methods, and safety can pose a big risk (death). Defibrillators are electronic devices that flow the shock electrical signal (pulse) to the heart muscle to maintain myocardial depolarization that is experiencing cardiac fibrillation (ventricular fibrillation or atrial fibrillation). The purpose of this study is make a defibrillator as a learning material so that anyone can have sufficient knowledge about the working principle and function of the defibrillator tool. This defibrillator is equipped with two wave selections namely monophasic and biphasic with asynchronous and synchronous modes, the energy provided ranges from 10-50 joules with use on tools 10, 20, 30, 50 joules. The energy will be flowed to the patient by pressing the Discharge button on Paddle which equivalently is adapted to humans. Energy disposal is controlled by a driver then the relay will work alternately from the first condensator then the second condensator to Paddle. Energy testing is done by 10 times using a defibrillator analyzer in a predetermined test point, the results of the monofacic wave measurement obtained by the error value of each setting with the smallest value of 0.0024% and the largest error value of 0.023%. To produce energy (joule) that appropriate capacitor is needed with real value. Bifasic waves cannot be tested because the defibrillator analyzer measuring instrument cannot detect the energy value (joule) capacitor that has been delivered.